Differentiation between populations of the Portuguese oyster, Crassostrea angulata (Lamark) and the Pacific oyster, Crassostrea gigas (Thunberg), revealed by mtDNA RFLP analysis - Boudry, Pierre; Heurtebise, Serge; Collet, Bertrand; Cornette, Florence; Gerard, André (Journal of Experimental Marine Biology and Ecology, 1998)
International audience Restriction fragment length polymorphisms of PCR-amplified mitochondrial DNA fragments were used to examine genetic differentiation between populations of the Portuguese oyster (Crassostrea angulata) and the Pacific oyster (Crassostrea gigas). The taxonomic status of C. angulata and C. gigas has often been questioned since no morphological or genetic differences had ever been observed between the two taxa. Samples identified as C. angulata, were collected from 16 sites located in southern Portugal and Spain and samples identified as C. gigas, from European and Asian sites. Of the six haplotypes observed, one was commonly found among oysters identified as C. gigas while another one was most frequent among oysters identified as C. angulata. Analysis of haplotype diversity among sites showed that samples originating from southern Portugal and Spain cluster with the Taiwanese sample. These results implicate Taiwan as the possible origin of European C. angulata populations. The ability to differentiate between these two previously indistinguishable taxa allowed us to identify a population in Portugal as mixed. These results open new perspectives for the study of characters previously described as varying between C. gigas and C. angulata, such as growth performance and disease susceptibility.